Poznavanje motenj požiranja pri srednjih medicinskih sestrah in zdravstvenih tehnikih v programih rehabilitacije in dolgotrajne oskrbe - Ogrin, Maja (Rehabilitacija (Ljubljana), 2018)
Background: Diagnostics and treatment of patients with dysphagia occurs within a multi-disciplinary team, in which nurses play an important role. Their action begins with early recognition of swallowing difficulties at the very beginning of the rehabilitation program. Further professional work and knowledge about the specific needs of patients with dysphagia significantly contribute to a comprehensive assessment and treatment of the disorder within nursing and rehabilitation institutions. We wanted to establish the level of knowledge about dysphagia and specific procedures of oral feeding among nurses working with persons with dysphagia. Methods: We invited 35 nurses to participate in the study, 18 from the University Rehabilitation Institute in Ljubljana and 17 from the Care and Working Centre in Ljubljana, working in the area of long-term nursing and care. To assess the level of knowledge about dysphagia, we used the Feeding Skills Questionnaire with permission of its author Alexandra Ameen. The questionnaire was translated and adapted to Slovenian speaking and cultural environment. Results: The results revealed some gaps in the knowledge about the disorder and its symptoms. There was a lack of knowledge of specific procedures that must be carried out prior to and during feeding a person with dysphagia among the employees of the Care and Working Centre. Conclusion: Our small-sample study identified strong and weak areas in the knowledge about swallowing disorders and specific feeding procedures among the nursing staff. The results will help us to prepare adequate content for further courses on dysphagia management for them.
Keywords: Deglutition Disorders; dolgotrajna oskrba; feeding; hranjenje; long-term care; motnje požiranja; nursing care; rehabilitacija; rehabilitation; swallowing disorders; vocational rehabilitation; zdravstvena nega